Analysis of Law Enforcement Related to the Fraud of Online Shopping Digital Payment System - Nabila Anisahaq; Kuswardani Kuswardani (IHSA Institute, 2022)
In the internet world, the potential for criminals to commit crimes is very large and very difficult to catch. It is because between people who are in this virtual world are mostly fictitious or the identity of the person is not real. The perpetrators violate the rules and norms of applicable law to gain more profit and enrich themselves. Online business makes the scammers are easier to take crime action. This research is normative legal research through a normative juridical approach. The data used secondary data covering primary legal material. The case with the transaction mode using QRIS has a relationship between Article 28 paragraph (1) of the ITE Law and Article 378 of the Indonesian Criminal Code, as seen from the elements that regulate the act on the article. In addition, it is also related to Article 4 of the Consumer Protection Law regulates the rights of consumers (QRIS users), which if violated is threatened with imprisonment for a maximum of 5 (five) years or a fine of at most 2 billion rupiahs. Using the Criminal Procedure Code as a basis to prove the non-conventional crime is very difficult to prove it because of the limitations of valid evidence according to Article 184 of the Criminal Procedure Code. In order to be more precisely prove the guilt of a person who committed a crime in the land of cyber/internet, the special law that can be used in this case is the Electronic Information and Transaction (ITE) Law which can be used to prove one's guilt in its evidence.